Analisis Miskonsepsi Buku Biologi Kelas X Pada Materi Keanekaragaman Hayati - Ulfa, Syarifah Widya; Azki, Salmiyani; Fadhillah, Lendy; Fauzianti, Windi; Marhamah, Agita; Fadila, Arif (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This research aims to identify misconceptions on concepts contained in biodiversity material in class 10 semester 2 with material topics which include: Biodiversity concepts, level diversity (genes, types and ecosystems), as well as diversity of spreading flora and fauna in Indonesia.The types of qualitative research using descriptive methods.Misconceptions identified are classified based on the categories of misidentification, oversimplification, obsolete concepts and terms, and undergeneralization.The results of this study indicate that there are 4 categories of misconceptions contained in the book in biodiversity materials, namely: undergeneralization, oversimplification, overgeneralization and misdenfitication.This misconception is what interferes with students' understanding of learning so that if it is not considered it will cause learning difficulties and will eventually lead to the low learning achievement of students.